Improvement of the system of education of highly qualified scientific personnel in the Republic of Belarus - Kosovskiy, Andrey A.; Klimkov, Alexey G. (Journal of the Belarusian State University. Economics, 2021)
The article presents an analysis of the effectiveness of measures taken by the state administration bodies of the Republic of Belarus in 2016 –2020 aimed at developing the system of education highly qualified scientific personnel. It is established that their implementation has allowed to increase the number of students and admission to doctoral studies by more than 1.5 times in 5 years, to preserve the country’s scientific personnel potential as a whole. The analysis of the dynamics of the highly qualified scientific personnel education over the past 5 years has been carried out with the identification of trends, the factors that negatively affect the development of the highly qualified scientific personnel education system have been identified. Taking into account these factors, additional incentives are presented to attract the most promising scientific personnel to the Belarusian science.